SOCIAL AND PSYCHOLOGICAL CLIMATE IN THE GENERAL SECONDARY EDUCATION INSTITUTIONS OF KYIV UNDER THE CONDITIONS OF THE MARTIAL LAW - Kostiantyn Lynov; Olena Merzliakova; Diana Sabol; Oksana Matviichuk (Borys Grinchenko Kyiv Metropolitan University, 2023)
This article shows indicators of the socio-psychological climate in general secondary education institutions of the capital of Ukraine in the conditions of martial law in the second year of the war. The authors conducted a survey of 420 educators, the staff of thirteen schools of Kyiv. Three methods were used: the method «Analysis and evaluation of the social and psychological climate of the team» (L.M. Karamushka); a method of assessing the psychological atmosphere of the team (according to A.F. Fiedler) and a questionnaire adapted by the department staff, containing 15 questions that characterize the attitude of teachers to work. The emotional attitude of teachers to the conditions of job was analysed; psychological atmosphere in the team; command settings etc. Four factors are key to establishing a favourable climate in schools: 1) relations with the principle, 2) relations with colleagues, 3) greater trust to the teacher who strives for self-realization, 4) clear organization of management activities. The teacher needs a higher level of trust. Most of all, teachers want to be able to demonstrate their own business qualities and build a clear relationship with the manager. It is important for teachers to be able to choose the directions of their activity, the content of their work, the ability to set the sequence of work at their own discretion within the defined terms, and to choose the method and time of their execution. During martial law, educators need more support and a sense of protection of their rights.